Planning and social change. Issue 3 (2nd October 2021) - Artner, Annamaria
Abstract : This article is an argument in favour of the central role of planning in any social change but particularly when a country embarks on the 'long road' to socialism. First, the role of planning in capitalism in the light of the most important distinctive features of capitalism will be examined. This will be followed by the description of the nature and difficulties of the transition from capitalism to socialism. Building on those the third section deals with the role and characteristics of planning on this road and provides empirical examples for the functioning of central planning in the transition to socialism using Hungary and China as case studies. The author concludes that central planning by a vanguard party-led government, well-armed with theoretical knowledge, and relying on the involvement of the people both in decision making and implementation, is the key for the success of the socialist project.